Feministas por opção, católicas pelo direito de decidir: vozes feministas na Igreja Católica - Silva, Julia do Carmo da (2015)
This study aims to examine how the Catholic feminist NGO Catholic for the Right to Decide (CRD) reconciles, through its discourses and practices, feminism and Catholicism. For this, we opted for the use of multilocated ethnography to explore different group entry fields. By analyzing in-person interviews, Facebook page, materials produced by the NGO and statements in the media, it can be concluded that the group has a highly professional and active militancy in different areas, which, combined with a modern individual vision, has as one of its main goals free will and autonomy of subjects. Also, thinking its actions and discourses requires a look at the power struggle in which the group falls within the religious field. By counteract the official voice of the Church, arguing new possibilities of being Catholic men and women, and trying to stake out a new position within this field, the group arises as an agent in the search for changes in the dominant structure.